2006
DOI: 10.1111/j.1399-3054.2006.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Annual changes in the concentration of minerals and organic compounds of Quercus suber leaves

Abstract: Mature leaves are the primary source of sugars, which give rise to many secondary metabolites required for plant survival under adverse conditions. In order to study the interaction of field-grown cork oak (Quercus suber L.) with the environment, we investigated the seasonal variation of minerals and organic metabolites in the leaves, using inductively coupled plasma atomic emission spectrometry, elemental analysis and nuclear magnetic resonance spectrometry. Statistical analysis showed that the data strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 38 publications
4
34
2
Order By: Relevance
“…Q. suber is a calcifugous tree that prefers acidic soils (Montero and Cañellas 1998); therefore, the lower leaf fall Mg content might be a strategy to cope with high levels of soil pH through decreasing the inputs of mobile cations to the soil. However, the low Mg concentration reported in the fresh leaves of these trees (Andivia et al 2010) in comparison with other studies (Oliveira et al 1996;Orgeas et al 2002;Passarinho et al 2006) suggests that the hypothesis of the Ca-Mg antagonistic effect is more realistic. This antagonist effect and its negative consequences on the nutritional status of cork oak trees point out the importance of a thorough assessment of soil conditions to assist in the detection of potential forest species best adapted to site-specific conditions.…”
Section: Effect Of Litter Nutrient Content On Soil Propertiescontrasting
confidence: 44%
“…Q. suber is a calcifugous tree that prefers acidic soils (Montero and Cañellas 1998); therefore, the lower leaf fall Mg content might be a strategy to cope with high levels of soil pH through decreasing the inputs of mobile cations to the soil. However, the low Mg concentration reported in the fresh leaves of these trees (Andivia et al 2010) in comparison with other studies (Oliveira et al 1996;Orgeas et al 2002;Passarinho et al 2006) suggests that the hypothesis of the Ca-Mg antagonistic effect is more realistic. This antagonist effect and its negative consequences on the nutritional status of cork oak trees point out the importance of a thorough assessment of soil conditions to assist in the detection of potential forest species best adapted to site-specific conditions.…”
Section: Effect Of Litter Nutrient Content On Soil Propertiescontrasting
confidence: 44%
“…Based on the data and considerations given above, we inferred that the unidentified signals of the 1 H and 13 C NMR spectra represented a species of cyclohexanepentol. Through a literature search, we found that these signals were in accordance with the NMR spectra of synthetic proto-quercitol (3,37,51) and extracted proto-quercitol from leaves of cork oak (47).…”
Section: Resultsmentioning
confidence: 83%
“…The assignments of the signals are marked on the spectra, i.e., compatible solute (Q or B) and atom (C or H) with the numberings given on the shown formulae of the compatible solutes. The assignments were based on previously published NMR data (3,16,37,47,51). The cells were grown in medium M1 with 1.0 M NaCl added.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cyclitol "quercitol" is commonly detected in species of Quercus (Passarinho et al, 2006;Popp et al, 1997) and may contribute to osmotic relations in some species of Eucalyptus (Merchant et al, 2005;. Quercitol is found in significant concentrations in Eucalyptus spp.…”
Section: Introductionmentioning
confidence: 99%